CHARACTERISTICS OF MANAGEMENT IN NAHDLATUL ULAMA -BASED ISLAMIC BOARDING SCHOOL SCHOOLS - Rd Khilal; Abdus Salam; Abdul Karim (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Study This aim analyzes internalization mark Ahlus Sunnah wal Jamaah (Aswaja) in system management Cottage Cipasung Islamic Boarding School, characteristics, structure, and governance institutional, pattern leadership of the kiai and the relationship with foundations and educational units, implementation functions management, and adaptation strategies to modernization without removing identity to -NU- an. Method study use approach with type studies Case study. Data collection techniques included in-depth interviews, observation, and documentation studies. Data analysis used the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and conclusion drawing and verification. Data validity testing was conducted through triangulation of sources and techniques, providing a check. The results of the study indicate that: 1)Internalization of Aswaja values ( tawassuth, tawazun, tasamuh, i'tidal ) functions as a governance principle that frames decision-making and organizational culture. 2)The organizational structure and governance are hybrid, combining the moral-charismatic authority of kiai with the formal governance of the foundation and the differentiation of educational units. 3) The Kiai's leadership pattern is charismatic - participatory through deliberation and delegation of authority in a synergistic relationship with the foundation and unit leaders. 4)The implementation of management functions (planning, organizing, implementing, monitoring-evaluation) is carried out systematically within the framework of Aswaja values with administrative and moral accountability. 5)The modernization adaptation strategy takes place selectively through strengthening accreditation, limited digitalization, improving human resources, and quality management, without eliminating the NU identity